2016
DOI: 10.1002/pat.3875
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical investigation of bilayer vascular grafts electrospun from aliphatic polyesters

Abstract: Electrospun biodegradable vascular grafts provide a wide range of design components from the selection of materials to the modification of fiber structure. In this study, both single layer and bilayer tubular scaffolds with inner diameter of 6 mm were electrospun from polycaprolactone with different molecular weights and poly(l‐lactide) caprolactone polymers. Bilayer scaffolds were designed by using different combinations of the polymer types in each layer and obtaining fiber orientation in outer layers. Scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…When comparing all samples regardless of polymer type, it is possible to notice the effect of fiber diameter on pore size results. Current literature confirms the case that fiber diameter affects the average pore area of the fibrous surface, and the average pore area increases with increasing fiber diameter 4,29 . The pore sizes of the samples follow a trend similar to the fiber diameter distributions (PLA8 < PCL10 < PLA10 < PLA/PCL), but considering the standard deviations, the differences between them are not very large.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…When comparing all samples regardless of polymer type, it is possible to notice the effect of fiber diameter on pore size results. Current literature confirms the case that fiber diameter affects the average pore area of the fibrous surface, and the average pore area increases with increasing fiber diameter 4,29 . The pore sizes of the samples follow a trend similar to the fiber diameter distributions (PLA8 < PCL10 < PLA10 < PLA/PCL), but considering the standard deviations, the differences between them are not very large.…”
Section: Discussionsupporting
confidence: 69%
“…Biocompatibility, biodegradability, and non‐toxic behavior are the crucial limits for the physical and chemical structures of the scaffolds 3 . Besides, a scaffold must have sufficient tensile strength and keep its mechanical integrity under certain loads 4 . Pore characteristic is one of the main structural parameters that come to the forefront in evaluating the performance of any fibrous webs for tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yalcin-Enis et al ( 2017) designed surfaces with randomly oriented fibers and oriented fibers using PCL and poly(L-lactide) caprolactone (PLC) with various molecular weights, and then they examined the mechanical strength of those surfaces. The study's findings showed that the molecular weight and surface orientation both affected the burst strength of the graft formations [12].…”
Section: Type Of Blood Vessel Burst Pressure (Mmhg) Referencementioning
confidence: 95%
“…Other potential application is their use as scaffolds for vascular tissue regeneration. [7][8][9] Regardless of application, nanofibrous tubes must meet certain requirements concerning their mechanical strength and stability. For example, vascular grafts need to be strong enough to withstand arterial pressure, 10 but they also need to withstand increased longitudinal and transverse strain as they integrate into the surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%